PERAN ORANG TUA DALAM MENGATASI ANAK PUTUS SEKOLAH PADA USIA SEKOLAH DUSUN TANJUNG BANJAR - Elisa Sulianti, Ni Made; Bahari, Yohanes; Fatmawati, Fatmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractAs for the formulation of the problem in this study is how the role of parents can overcome school dropouts. This study aims to find out and describe the role parents play in overcoming school dropouts. This study uses a description method with a qualitative approach. Data collection techniques in this study used observation, interviews, and documentation. As for the information in the study as many as 6 people, namely 2 children an their parents, 2 junior high school children along with their parents and 2 high school children and their parents, the results of this study indicate that the role of parents in including as educators, parents have done their roles like (affective, cognitiv, psychomotor) well, the role of parents as motivations, parents have carried out their roles but are still not maximal in the from of giving motivation such as advice, reprimand, praise and gifts as a from of motivation so that children are motivated to continue their education, his parents provide moral support and motivation but not materially. And in the from of providing facilitators, parents provide learning facilies that are still inadequate, meaning that there is no provision of faciliteis that can support their children?s educational achievements, so that the results of parents? research are not optimal in their role as facilitators. Keywords: The Role Of Parents, School Dropouts, School Age